Parental‐couple separation during the transition to parenthood - Åsa Gamgam Leanderz; Jenny Hallgren; Maria Henricson; Margaretha Larsson; Caroline Bäckström (Wiley, 2021)
Abstract Aim To evaluate factors associated with parental separation during the parenthood transition. Design Prospective, longitudinal and explorative. Methods This is a quantitative longitudinal study of N784 subjects throughout the pregnancy journey with multivariate regression analysis of survey data derived from three validated measurement scales; the Sense of Coherence scale, the Multidimensional Scale of Perceived Social Support and the Perceived Quality of the Dyadic Relationship scale conducted 2014-2016. Results N17 participants separated at 2 years. Parental separation was significantly greater for those women and partners with low or changing sense of coherence, perceived social support and perceived quality of the parental‐couple relationship indexes. Partners with a change in sense of coherence (p: .003) and perceived quality of the parental‐couple relationship (p: .020) between 1 week and 2 years were at greater risk for separation. Attending professional preparatory support with a partner for women (p: .013) and attending the "Inspirational Lecture" for partners (p: .046) were, to a lesser extent, associated with a risk of parental separation.